Impacts of COVID-19 on Household Welfare in Tunisia - Deeksha Kokas; Gladys Lopez-Acevedo; Abdel Rahmen El Lahga; Vibhuti Mendiratta (Institute of Labor Economics (IZA), 2020)
COVID-19 is likely to have a large impact on the welfare of Tunisian households. First, some individuals might be more vulnerable to contracting the disease because their living conditions or jobs make them more susceptible to meeting others or practicing social distancing. Lack of adequate access to health insurance, overcrowded living conditions, and low access to water at home are reasons that make the Tunisian poor more susceptible to getting infected or not being able to seek health care in the event that they contract COVID-19. In addition, the elderly in the poorest households could be more susceptible to COVID-19 due to higher prevalence of intergenerational households among the poor. Second, many sectors of the labor market have experienced an economic slowdown, and those employed in these sectors are likely to experience disproportionate effects. Combining the labor shock and price shock simultaneously, the simulations in this paper show an increase in poverty of 7.3 percentage points under a more optimistic scenario and 11.9 percentage points under the pessimistic scenario, and individuals in sectors such as tourism and construction are expected to fall into poverty due to COVID-19. The paper estimates that the government's compensatory measures targeted toward the hardest hit are expected to mitigate the increase in poverty. Specifically, the increase in poverty will be 6.5 percentage points under the optimistic scenario if mitigation measures are in place vis-à-vis in their absence, when the increase in poverty is 7.3 percentage points.
Keywords: J16; J21; O54; 330; COVID-19; Tunisia; labor income; consumption